2008
DOI: 10.1007/s11746-008-1331-x
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Influence of Alumina Catalysts Doped with Tin and Zinc Oxides in the Soybean Oil Pyrolysis Reaction

Abstract: The pyrolysis of vegetable oils consists of cracking triglycerides to produce smaller molecules. A mixture of hydrocarbons and oxygenated compounds, such as carboxylic acids and aldehydes, is obtained as the product and which can be separated by fractional distillation. When the reaction is carried out in the absence of catalysts (thermal cracking), a great quantity of these oxygenated compounds is obtained. Thus, the presence of those oxygenated compounds in the products results in a high level of acidity, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
2
14
0
5
Order By: Relevance
“…Catalytic pyrolysis of fatty acids and triglycerides over different catalysts has already been studied by other authors with the main aim of transforming these compounds into aliphatic hydrocarbons [28][29][30][31][32][33][34][35][36][37]. Xu et al [33] compared different catalysts and according to their studies the most promising biofuels are obtained when the pyrolysis is carried out in the presence of a basic catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic pyrolysis of fatty acids and triglycerides over different catalysts has already been studied by other authors with the main aim of transforming these compounds into aliphatic hydrocarbons [28][29][30][31][32][33][34][35][36][37]. Xu et al [33] compared different catalysts and according to their studies the most promising biofuels are obtained when the pyrolysis is carried out in the presence of a basic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, the reaction products are heavily dependent on the catalyst type and reaction conditions and can range from dry gas to light distillate, liquefied petroleum gas and gasoline. Quirino et al [30] studied the catalytic pyrolysis of soybean oil over alumina doped with Tin and Zinc oxides and reached a significant reduction of oxygenated compounds in the biofuels obtained. On the other hand, according to previous results, in which different catalysts (natural zeolite, HZSM-5, char, ash and activated alumina) were tested on the pyrolysis of sewage sludge, the most promising results for the deoxygenation of fatty acids and their transformation into aliphatic hydrocarbons were obtained with activated alumina [39].…”
Section: Introductionmentioning
confidence: 99%
“…Enquanto os segundos não alteram significativamente a cadeia carbônica, os primeiros também são associados à reações de clivagem e aromatização das cadeias para formação de benzeno e derivados. 25,26 Óxidos básicos como o óxido de magnésio e cálcio também podem ser utilizados, porém estes estabilizam os ácidos graxos formados na primeira etapa de pirólise, de modo que o bio-óleo obtido fica mais ácido. A modificação da atmosfera de reação se apresenta como outra variável para se alterar a seletividade dos produtos.…”
Section: Aumentando Ainda Mais a Temperatura: A Pirólise E Seus Inúmeunclassified
“…Quirino et al 37 cracked soybean oil between 350 and 400 ºC, in the presence of catalysts based on Zn and on Sn oxides, co-precipitated with alumina. After separation of the aqueous and organic phases, and further distillation of the organic phase in four fractions F1, F2, F3 and F4, the authors observed that the presence of the catalysts during thermocatalytic cracking led to an increase in the yield of liquid products and to a decrease in the oxygenated compounds in the organic fraction.…”
Section: Thermo-catalytic Decomposition Of Triglyceridesmentioning
confidence: 99%